Pengaruh Kinerja Tutor terhadap Kemandirian Belajar Mahasiswa dalam Problem Based Learning di Fakultas Kedokteran UISU - Martinus Martinus; Gandes Retno Rahayu; Ova Emilia (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2012)
Background: For two years implementation of PBL in Faculty of Medicine Islamic University of Sumatera Utara several phenomenon should be evaluated such as various performance of tutor in facilitating PBL and student’s self study not much. This research aimed to evaluate the relationship between tutor performance and student’s self study and reporting process in PBL.Method: This was observational analytical research, cross sectional study with population of all students of Faculty of Medicine Islamic University of Sumatera Utara. Primary data was collected from June to August 2009. Instrument used were tutor performance evaluation questionnaire, self learning activity evaluation questionnaire and student’s self study and reporting process in PBL questionnaire with Likert scale. Kruskall Wallis test was used to assess the relationship between tutor and student performance.Results: Average score of tutor performance on first year was higher compared to the second year students (p=00,32). There is significant difference in student’s self study and report process in PBL between high and moderate tutor performance’s group (p=0,000; p=0,000), high and low tutor performance’s group (p=0.007, p=0,008), but not significant difference between moderate and low tutor performance’s group (p=0,111, 0,280).Conclusion: Tutor performance is related to higher level of student’s self study and report process in PBL.